До вивчення репродуктивної здатності деяких лікарських рослин, інтродукованих в Донецькому ботанічному саду НАН України - Птиця, В.В. (Промышленная ботаника, 2004)
Reproductive capacity of Inula helenium L., Origanum puberulum (G. Beck) Klokov, Pulsatilla nigricans St rck under the introduction has been studied. The results of investigation of sprouting energy and laboratory seed germination are presented. For the first time the methods of O. puberulum propagation by green cuttings and P. nigricans - by particles without digging out the maternal plant under conditions of the Donetsk Botanical Gardens have been used. It was fixed that rootage success changes depending upon phenologic phases during which the propagation by cuttings and particles was conducted.